PENGARUH PENGGUNAAN BUKU MONTESSORI TERHADAP KEMAMPUAN MEMBACA PERMULAAN - Dessy Dwitalia Sari; Tika Puspita Widya Rini (JURNAL PENDIDIKAN DASAR, 2022)
Online learning during the Covid-19 pandemic has an impact on the early reading ability of grade 1 elementary school students. Online learning that is carried out in full makes the teacher unable to find out why students are still not fluent in reading. The data found some students do not know the letters and how to pronounce them. The purpose of this study was to determine the initial reading ability of first graders at SDN Pasar Lama 1 Banjarmasin using a Montessori reading book. In addition, to determine the significant effect on learning to use Montessori reading books in improving early reading skills. This study uses an experimental method with t-test analysis. The results showed that the students' initial reading ability increased. The results of the t-test showed a value of 0,026 0.05, so it can be said that there was a significant difference in the students' initial reading ability who used Montessori reading books with students who studied without using Montessori reading books. Learning to use Montessori reading books has an effect on students' initial reading ability.